A valência do verbo colocar e as diáteses de colocação - Polyana Prates de Oliveira Plais (2017)
This study was elaborated from a descriptive perspective and follows Perinis (2008, 2015)proposal of verbal description, which is the base of the Valency Dictionary of BrazilianPortuguese Verbs Project, VVP in Portuguese, of which this research is part. We started withthe verbal categorization proposal made by Levin (1993) for English verbs and, from her dataset, we chose the Verbs of putting category whose members we translated into the Portugueseand among which we highlighted our object of study, the verb to put. Our first and primarygoal, therefore, was to describe the valency of this verb. In addition, we also elaborated andrecorded the valency of 24 additional verbs from the same set of Levin, which would becompared later to meet more specific goals. The data that gave us the first notions about theseverbs came from the dictionary of Borba et al. (1990) and our first hypothesis was that inBrazilian Portuguese, these verbs would not be classified in the same way as put, but mayoccur in others diatheses. From the analysis of the PUTTING scheme, we define the threeputting diatheses that we later identified in the valencies of the studied verbs. Confirming ourhypothesis, besides these, we find other diatheses that did not evoke the PUTTING scheme,such as SAYING, present in the valencies of dicendi or communication verbs (COUTO,2017). Another goal of the research was to evaluate the viability of establishing verbal classesaccording to diatheses and, for this we divided our 25 verbs by observing the presence of thePUTTING diatheses. The result led us to conclude that this proposal of categorization wouldbe a large work, considering the amount of diatheses that we have been elaborating andmoreover, it would not be sufficiently relevant for the study of verbal syntactic-semanticbehavior. We believe, however, that to analyze and compare the valences in order to identifythose verbs that have the same set of diatheses, which is relatively exceptional, would be agreat step for studies in this area.